2020
DOI: 10.1038/s41598-020-70487-z
|View full text |Cite
|
Sign up to set email alerts
|

Sorption, solubility and cytotoxicity of novel antibacterial nanofilled dental adhesive resins

Abstract: Dental adhesives hydrolyze in the mouth. this study investigated the water sorption (SoR), solubility (SoL) and cytotoxicity (cYto) of experimental adhesives containing nitrogen-doped titanium dioxide nanoparticles (n_tio 2). Specimens (n = 15/group [SOR, SOL]; n = 10/group [CYTO]) of unaltered Clearfil SE Protect (CSP), OptiBond Solo Plus (OSP), Adper Scotchbond (ASB) and experimental adhesives (OSP + 25% or 30% of N_TiO 2) were fabricated, desiccated (37 °C) and tested for SOR and SOL according to ISO Specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Recently, research incorporating TiO 2 NPs in dental adhesives concluded that they had enhanced biocompatibility with reduced solubility and water sorption when compared to the conventional adhesives used in dentistry. Thus, the usage of these NPs is highly recommended in currently available adhesive dentistry [ 333 ]. Another research work elaborated that TiO 2 NPs added to self-adhesive cements revealed a maximum degree of conversion (DC) when compared to their conventional types [ 334 ].…”
Section: The Titanium Oxide Npsmentioning
confidence: 99%
“…Recently, research incorporating TiO 2 NPs in dental adhesives concluded that they had enhanced biocompatibility with reduced solubility and water sorption when compared to the conventional adhesives used in dentistry. Thus, the usage of these NPs is highly recommended in currently available adhesive dentistry [ 333 ]. Another research work elaborated that TiO 2 NPs added to self-adhesive cements revealed a maximum degree of conversion (DC) when compared to their conventional types [ 334 ].…”
Section: The Titanium Oxide Npsmentioning
confidence: 99%
“…According to previous studies, current dental adhesive resins are formulated using a combination of hydrophilic and hydrophobic components [ 18 ] that phase-separate when applied onto water-rich tissues [ 19 ]. This chemical instability leads to incomplete envelopment of exposed collagen fibrils and the establishment of porous hybrid layers that are prone to failure by biodegradation, hydrolysis, esterases, and biofilms [ 20 ]. This significant problem has precipitated the execution of several studies to improve the physical, chemical, and biological properties of current polymer formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 , anatase, rutile, or brookite) is known for its relevant physical, chemical, antimicrobial, and biocompatibility properties [ 33 ]. Nanoparticles of TiO 2 (TiO 2 -np) are typically white, have diameters around 25 nm, have high refractive index, are corrosion resistant, display high microhardness values [ 20 , 34 ], and were demonstrated to be effective against numerous microorganisms, including Candida albicans , Staphylococcus aureus , Pseudomonas aeruginosa , Escherichia coli , and Lactobacillus acidophilus [ 35 ]. However, despite these relevant characteristics, TiO 2 -np have large bandgaps (3.2204 eV, for anatase) and require the utilization of UV irradiation to generate different types of reactive oxygen species (ROS) [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In dentistry, TiO 2 nanoparticles have been used to improve the fracture resistance of endodontically treated teeth [14], osseointegration of dental implants [15], antibacterial potential of a material [13], and bonding to human teeth by incorporating them in the adhesives [16]. In a recent study, the addition of TiO 2 nanoparticles in experimental dental adhesives demonstrated comparable water sorption, solubility, and biocompatibility with unaltered adhesives, advocating the use of these particles in adhesive dentistry [17]. In another study, it was reported that self-adhesive resin cements containing TiO 2 displayed a superior degree of conversion (DC) to their unaltered counterparts [18].…”
Section: Introductionmentioning
confidence: 99%